A high temperature resistant support film and preparation method thereof

By using anti-adhesive coating, modified polyurethane adhesive layer and wear-resistant coating in the base film, the problem of poor stability of the base material at high temperatures is solved, and efficient bottoming function and cost reduction are achieved.

CN115742514BActive Publication Date: 2024-12-24安徽科能新材料环保科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211442041.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2024-12-24
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The existing bottom support materials are difficult to maintain stability at high temperatures and cannot effectively carry the semi-finished high-temperature tires, resulting in the decomposition of adhesives and the failure of the composite film layer structure during processing, and the metal bottom support plate is costly and inconvenient to shift.

Method used

Using a high-temperature resistant backing film composed of an anti-adhesive coating, a modified polyurethane adhesive layer and a wear-resistant coating, the anti-adhesive coating and a wear-resistant coating are provided on the PET layer, combined with the thermal decomposition of the modified polyurethane adhesive layer. The temperature is increased, friction and wear is reduced, and the film is prepared by hot pressing.

Benefits of technology

It improves the high temperature resistance and service life of the base film, prevents rubber from adhesion to the film surface, reduces friction and wear, reduces cost and facilitates displacement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115742514B_ABST
    Figure CN115742514B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of coating composite materials, and specifically discloses a high-temperature resistant backing film and a preparation method thereof. The high-temperature resistant backing film of the present application includes, from the inside to the outside, an anti-stick coating, a first PET layer, an intermediate layer, a second PET layer and a wear-resistant coating, a first adhesive layer is arranged between the first PET layer and the intermediate layer, a second adhesive layer is arranged between the second PET layer and the intermediate layer, the anti-stick coating is attached to the first PET layer, and the wear-resistant coating is attached to the second PET layer; and the first adhesive layer and the second adhesive layer are both modified polyurethane adhesive layers. The present application sets the first adhesive layer and the second adhesive layer in the composite backing film as modified polyurethane adhesive layers with heat-resistant properties, so that the backing layer is easy to carry the high-temperature tire semi-finished product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating composite materials, and in particular to a high temperature resistant support film and a preparation method thereof. Background Art

[0002] Tires are annular elastic products used for vehicle driving and aircraft landing. They can absorb vibrations and external impacts caused by uneven roads to ensure the driving quality of drivers. Tires are the main processed products in the rubber industry, and the amount of rubber consumed by them accounts for 50-60% of the total rubber consumption.

[0003] In the tire processing technology, metal support plates are often used to support high-temperature semi-finished tires. Since metal support plates have good high-temperature resistance and anti-adhesion properties, it is convenient for workers to perform related processing operations on the semi-finished tires. During the processing of the semi-finished tires, the metal support plates are easily scratched by other processing equipment, or worn by friction with the ground when the metal support plates are moved. At the same time, the cost of replacing such metal support plates is high, and the weight of the metal support plates is large, which makes it inconvenient for workers to move them. Among the existing support materials, organic composite films are a low-cost material, and different coatings can be set to obtain better friction resistance and anti-adhesion properties. However, it is difficult to maintain good stability at high temperatures and is not suitable for supporting high-temperature semi-finished tires.

[0004] In view of the above technology, the inventors believe that in the process of processing high-temperature tire semi-finished products, the high temperature will cause the adhesive between the existing composite films to decompose, resulting in failure of the composite film layer structure. Therefore, it is necessary to develop a high-temperature resistant bottom composite film material. Summary of the invention

[0005] In order to improve the high temperature resistance of the adhesive between the middle layers of the composite support film, the present application provides a high temperature resistant support film and a preparation method thereof.

[0006] In the first aspect, the present application provides a high temperature resistant support film, which adopts the following technical solution:

[0007] A high temperature resistant backing film, characterized in that it includes, from the inside to the outside, an anti-stick coating, a first PET layer, an intermediate layer, a second PET layer and a wear-resistant coating, a first adhesive layer is arranged between the first PET layer and the intermediate layer, a second adhesive layer is arranged between the second PET layer and the intermediate layer, the anti-stick coating is attached to the first PET layer, and the wear-resistant coating is attached to the second PET layer; and the first adhesive layer and the second adhesive layer are both modified polyurethane adhesive layers.

[0008] By adopting the above technical solution, an anti-stick coating is provided on the first PET layer in contact with the high-temperature rubber semi-finished product to prevent the rubber from sticking to the film surface, thereby affecting the processing quality of the rubber tire. By providing a high-temperature resistant modified polyurethane adhesive layer in the middle layer between the first PET layer and the second PET layer, it is possible to effectively prevent the adhesive layer from being thermally decomposed by high temperature, thereby causing the composite film layer structure to become loose. By providing a wear-resistant coating on the second PET layer in contact with the ground, the wear on the PET film surface caused by relative friction is reduced during the processing of the auxiliary tire semi-finished product, thereby increasing the service life of the bottom film. Optionally, the thickness of the first PET layer and the second PET layer are both set to 75-100 microns, and the thickness of the first adhesive layer and the second adhesive layer are both set to 25-35 microns, which can improve the integrity between the composite layer structures.

[0009] Preferably, the modified polyurethane adhesive layer comprises a first component and a second component, wherein the first component comprises the following raw materials in parts by weight: 60-80 parts of diphenylmethane diisocyanate (MDI), 42-48 parts of bisphenol A diglycidyl ether (DGEBA), 15-20 parts of a first polyol and 0.5-0.7 parts of a first catalyst.

[0010] The second component comprises the following raw materials by weight: 30-36 parts of a second polyol, 12-16 parts of a chain extender, 0.7-0.9 parts of a second catalyst, 3-6 parts of a crosslinking agent and 0.8-1.2 parts of nano zirconium dioxide powder.

[0011] By adopting the above technical scheme, a composite modification method combining chemical modification and physical modification is used in polyurethane molecules, and bisphenol A diglycidyl ether is used to react the epoxy functional group it carries with isocyanate, and under the action of a catalyst, oxazolidinone is generated and introduced into the polyurethane molecule. Since oxazolidinone has a rigid five-membered ring structure, it has a large cohesive energy, and the bond energy of the carbon-oxygen double bond is large, resulting in good high temperature resistance, thereby increasing the thermal decomposition temperature of polyurethane. Heat-resistant filler nano zirconium dioxide powder is mixed into the modified polyurethane rubber material. Since the chemical properties of zirconium dioxide are inactive, it will not affect the reaction system, and it has a high thermal insulation coefficient, which can effectively improve the high temperature resistance of polyurethane. And aromatic diisocyanates are mainly synthesized using toluene as raw material, containing a benzene ring structure, and therefore also have good heat resistance.

[0012] Preferably, the method for preparing the modified polyurethane adhesive layer comprises the following steps:

[0013] S1. Preparation of the first component: Under a vacuum degree of less than 0.36 KPa, bisphenol A diglycidyl ether is heated to 115-120°C to remove moisture for 1.5-2 hours, a first catalyst is added, and the temperature is gradually increased to 90-95°C at a rate of 1-2°C / min, and stirred for 0.5 hours. After the first catalyst is completely dissolved, diphenylmethane diisocyanate is added dropwise under vacuum conditions, and the reaction is stirred at a speed of 500-550 r / min for 4-5 hours to obtain modified diphenylmethane diisocyanate;

[0014] S2, under a vacuum degree of less than 0.36 KPa, heat the first polyol to 105-115°C to remove moisture for 1-2 hours, release the vacuum when the moisture mass is less than 0.06%, cool to 30-40°C, add the modified diphenylmethane diisocyanate prepared in step S1, gradually heat to 75-80°C at a rate of 1-2°C / min, react for 2.5-3 hours, cool to 30-40°C, degas and seal for storage;

[0015] S3, preparation of the second component: under a vacuum degree of less than 0.36 KPa, heat the second polyol to 100-110°C to remove moisture for 2.5-3h, when the moisture mass is less than 0.06%, release the vacuum, cool to 30-40°C, add the second catalyst, chain extender, crosslinking agent and nano zirconium dioxide powder in sequence, mix, stir for 30min, degas and seal for storage;

[0016] S4, mixing the first component and the second component at a vacuum degree below 0.36 KPa, wherein the mass ratio of the first component to the second component is 1:(0.5-0.7), and magnetically stirring at a speed of 280-300 r / min to obtain a modified polyurethane rubber;

[0017] S5. After surface pretreatment of the intermediate layer, the modified polyurethane adhesive prepared in step S4 is evenly coated on the intermediate layer, the first PET layer and the second PET layer are attached to both sides of the intermediate layer, and the modified polyurethane adhesive layer is obtained after curing at room temperature for 2-3 hours.

[0018] By adopting the above technical scheme, it is necessary to carry out pre-dehydration and drying in the process of preparing polyurethane to prevent the isocyanate group from being consumed by water, so that it cannot fully react with the polyol, thereby affecting the bonding performance of the polyurethane glue. The stirring speed needs to be controlled during the synthesis reaction to ensure that the reaction proceeds smoothly. When the stirring speed is too fast, the friction gap between the stirring paddle and the material will bring air into the reaction system, and bubbles will be generated inside the rubber, thereby reducing the mechanical properties of the polyurethane glue. When the stirring speed is too slow, the raw materials in the system will be unevenly mixed and local overheating will occur, resulting in gelation. In addition, during the polymerization process, it is necessary to adopt a gradual heating method to prevent the reaction rate from increasing exponentially, resulting in excessively high local temperatures in the system. In addition, affected by the friction resistance within the generated high molecular weight molecular chain segments, the viscosity increases rapidly, resulting in more difficult stirring and heat dissipation, and gelation or even explosion is prone to occur, so that the reaction is terminated.

[0019] Preferably, the anti-stick coating is an organic antimony-modified silicone-based anti-stick coating, and the organic antimony-modified silicone-based anti-stick coating comprises the following components in parts by weight: 15-20 parts of methyl vinyl MQ silicone resin, 4-7 parts of vinyl silicone oil, 2-3 parts of hydrogen-containing silicone oil, 0.3-0.7 parts of antimony tribenzoate and 0.5-0.8 parts of nano-silica powder.

[0020] By adopting the above technical scheme, methyl vinyl MQ silicone resin is used as a polysiloxane resin, in which the organic polysiloxane has a helical structure, so that its molecules have a smaller force and surface tension, and the silicon oxygen bond is a polar bond, which is easy to form a hydrogen bond, so that it can be evenly spread on the surface of the PET layer; nano silicon dioxide powder is added for further modification. The addition of nano silicon dioxide powder will cause physical adsorption and physical entanglement with the coating, greatly improving the crosslinking density and tensile strength of the coating. At the same time, by controlling the amount of nano silicon dioxide powder added, the surface roughness of the coating is changed, and then the surface free energy of the coating is reduced to achieve a better anti-sticking effect. By adding high temperature resistant filler antimony tribenzoate, the organic antimony heat-resistant material has excellent initial aging resistance and thermal stability, low melt viscosity during processing, and good synergistic effect with other reagents.

[0021] Preferably, the method for preparing the organoantimony-modified organosilicon-based anti-stick coating comprises the following steps:

[0022] S1, sequentially mix methyl vinyl MQ silicone resin with vinyl silicone oil and hydrogen-containing silicone oil, stir ultrasonically for 20-40 minutes, add Pt catalyst, heat to 35-40° C., react for 30-40 minutes, and obtain a liquid phase reaction solution;

[0023] S2, first add antimony tribenzoate to the liquid phase reaction solution in step S1, mix, stir for 5 minutes, then add nano silicon dioxide powder, mix, stir for 10 minutes, and stand at room temperature for 30 minutes to prepare a preliminary coating;

[0024] S3, after the surface of the first PET layer is pretreated, the preliminary coating prepared in step S2 is evenly coated on the surface of the first PET layer, dried at 80-90° C. for 30 min, cured at a constant temperature for 4 h, and naturally cooled to obtain an organic antimony-modified silicone-based anti-stick coating.

[0025] By adopting the above technical scheme, methyl vinyl MQ silicone resin, vinyl silicone oil, and hydrogen-containing silicone oil are used as siloxane monomer raw materials, and an addition reaction is carried out under the action of a platinum catalyst to generate an addition-type silicone coating with a high crosslinking density, and antimony tribenzoate and nano-silicon dioxide powder are added thereto in the form of fillers to reduce the surface free energy of the coating and improve its physical and chemical properties. Antimony tribenzoate is added as an organic antimony heat-resistant material to achieve a heat-insulating effect on the surface of the coating to prevent the high-temperature semi-finished rubber tire from affecting the film surface of the first PET layer; nano-silicon dioxide powder is added to improve the tensile strength, hardness and anti-sticking properties of the coating from the two levels of physical entanglement and chemical effect, so that the prepared anti-sticking coating can meet the requirement of not adhering to the semi-finished rubber tire, thereby using physical modification to improve the overall anti-sticking and high-temperature resistance of the coating.

[0026] Preferably, the wear-resistant coating is a silicone-modified bisphenol A epoxy resin wear-resistant coating.

[0027] By adopting the above technical scheme, bisphenol A epoxy resin, as a high-yield epoxy resin, not only has the advantages of low cost and easy availability of raw materials, but also the benzene ring in the structural unit of bisphenol A epoxy resin gives it certain heat resistance and rigidity, and the isopropyl group can reduce the interaction force between resin molecules, making it have good toughness; using organosilicon compounds to modify bisphenol A epoxy resin, the interaction force between organosilicon molecules is small, and there is a linear relationship between its cross-linking degree and hardness and flexibility, so the hardness and flexibility can be adjusted by changing the structure of organosilicon polymers, and the cross-linking degree can be increased to improve the hardness. The coating obtained by chemical modification can effectively reduce the friction coefficient of the coating surface and enhance the wear resistance, and the organosilicon compound can greatly reduce the internal stress of the epoxy resin, thereby improving the toughness and heat resistance of the bisphenol A epoxy resin coating.

[0028] Preferably, the middle layer includes staggered main isolation strips and secondary isolation strips, the main isolation strips cross each other to form a 5mm*5mm grid structure, the main isolation strips are made of polyurethane material, and the secondary isolation strips are made of silicon oxide nanofiber material.

[0029] By adopting the above technical solution, by setting the main isolation strip of polyurethane material in the middle layer as a grid structure, the reinforcement effect of the bottom support film can be achieved, the integrity between the composite layer structures can be improved, and the polyurethane material has good stability, chemical resistance, resilience, thermal insulation and mechanical properties, and has smaller compression deformation. By setting a secondary isolation strip made of silicon oxide nanofiber material, the shielding effect of the modified polyurethane adhesive layer on ultraviolet rays can be improved. At the same time, silicon oxide nanofiber can also be used as a reinforcing filler to further improve the hardness, shear strength and thermal stability of the adhesive layer, but the toughness of the adhesive layer will be slightly reduced. Optionally, the main isolation strip is set to 80-120tex and the secondary isolation strip is set to 20-30tex. While achieving the above effects, it will not cause marks on the high-temperature rubber semi-finished products during the tire processing process, affecting the production quality of the tire.

[0030] Preferably, the first polyol and the second polyol are one or more of ethyl adipate diol (PEA), polycarbonate diol (PCDL) and polyhexylene adipate diol (PDA).

[0031] By adopting the above technical solution, ester polyols such as ethanol adipate diol are added to form soft segments in polyurethane that give it flexibility, and react with isocyanate to form polyurethane. In addition, ester polyols contain more polar ester groups, so their cohesive energy is stronger, and the prepared polyurethane adhesive can have better mechanical properties, heat stability, wear resistance and light resistance.

[0032] Preferably, the chain extender is one or more of diethanolamine, triethanolamine and monoethylenetriamine.

[0033] By adopting the above technical solution, the addition of low molecular weight amine chain extenders can react with the linear polymer functional groups to expand the molecular chain, and can not only react with the NCO group to generate carbamate group chain extension, but also have a certain catalytic effect in the polyurethane synthesis process because the substituted nitrogen atom has a certain alkalinity, and can adjust the reaction rate, thereby producing rapid crosslinking and chain extension. By introducing low molecular weight amine chain extenders to change the ratio of soft segments and hard segments in the copolymer, the molecular weight of the polyurethane is increased, and the stability of the emulsion is enhanced.

[0034] Preferably, the first catalyst and the second catalyst are one or more of dimethylcyclohexylamine (DMCHA), dimethylethanolamine (DMEA) and triethylenediamine (TEDA).

[0035] By adopting the above technical scheme, a tertiary amine catalyst is added to promote the reaction rate of the chemical reaction in the polyurethane reaction system. By promoting the reaction progress of the main reaction, the occurrence of side reactions can be reduced and suppressed, thereby obtaining a better molecular structure; it can also promote the chain growth reaction of small and medium molecular weight compounds, allowing the molecular chain to grow rapidly and improve the molecular chain.

[0036] Preferably, the crosslinking agent is diethylenetriamine (DETA).

[0037] By adopting the above technical solution, diethylenetriamine is added to form a regular cross-linked network structure in the polyurethane, so that the tensile strength first increases and then decreases, and the elongation at break decreases. In addition, the chemical cross-linked structure is relatively stable, and the changes affected by temperature are irreversible. The cross-linked structure has a great influence on the intermolecular force, especially the hydrogen bonding effect. The increase in the degree of cross-linking will reduce the degree of hydrogen bonding, improve the performance of the polyurethane glue at high temperature, and enable the material to obtain excellent mechanical properties and oil resistance, wear resistance, heat resistance and ozone resistance. At the same time, the cross-linked structure formed by adding diethylenetriamine also affects the crystallinity inside the polyurethane, and a small amount of cross-linked structure will reduce the crystallinity.

[0038] In a second aspect, the present application provides a method for preparing a high temperature resistant support film, comprising the following steps:

[0039] S1, heating the coating of the anti-stick coating to 40-55° C., applying the coating of the anti-stick coating on the surface of the first PET layer to form an anti-stick coating, then heating the coating of the wear-resistant coating to 60-70° C., applying the coating of the wear-resistant coating on the surface of the second PET layer to form a wear-resistant coating, and standing the first PET layer and the second PET layer coated with the coating at room temperature for 2-3 hours for curing;

[0040] S2. Coat the side of the first PET layer away from the anti-stick coating with a modified polyurethane adhesive to form a first adhesive layer, then cover the intermediate layer on the first adhesive layer, and coat the side of the second PET layer away from the wear-resistant coating with a modified polyurethane adhesive to form a second adhesive layer, and then bond the side of the second PET layer coated with the second adhesive layer to the side of the intermediate layer away from the first adhesive layer, and hot press the above materials at a temperature of 60-80°C and a pressure of 0.3-0.4MPa for 1-2s to obtain a high temperature resistant base film.

[0041] By adopting the above technical solution, the various layers of structure are assembled and bonded in the order of their functions, and then the film is formed by hot pressing. By controlling the temperature and pressure within the appropriate range, not only can the curing speed of the adhesive layer be accelerated, the production efficiency of the bottom film product be improved, but also the bubbles between the layers of structure can be discharged to prevent the film surface from wrinkling and unevenness, which affects the appearance quality of the bottom film product.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. The present application uses a composite modification method combining chemical modification and physical modification in polyurethane molecules, using bisphenol A diglycidyl ether to react the epoxy functional group with isocyanate, and under the action of a catalyst, an oxazolidinone with high temperature resistance is generated and introduced into the polyurethane molecule. Heat-resistant filler nano zirconium dioxide powder is mixed into the modified polyurethane rubber material. Since zirconium dioxide has a high thermal insulation coefficient, the high temperature resistance of polyurethane can be effectively improved. And aromatic diisocyanates are mainly synthesized with toluene as raw material, containing a benzene ring structure, so they also have good heat resistance; 2. The present application sets an organic antimony-modified silicone-based anti-sticking coating on the surface of the first PET layer. The addition of nano silicon dioxide powder will cause physical adsorption and physical entanglement with the coating, greatly improving the crosslinking density and tensile strength of the coating. At the same time, by controlling the amount of nano silicon dioxide powder added, the surface roughness of the coating is changed, thereby reducing the surface free energy of the coating, and achieving a better anti-sticking effect. Adding high temperature resistant filler antimony tribenzoate, the organic antimony heat resistant material has excellent initial aging resistance and thermal stability, low melt viscosity during processing, and good synergistic effect with other reagents;

[0044] 3. The present application sets a wear-resistant coating of bisphenol A epoxy resin modified with organosilicon on the surface of the second PET layer. The bisphenol A epoxy resin is modified by organosilicon compounds. The interaction force between organosilicon molecules is small, and there is a linear relationship between the degree of crosslinking and the hardness and flexibility. Therefore, the hardness and flexibility can be adjusted by changing the structure of the organosilicon polymer, and the degree of crosslinking can be increased to improve the hardness. The coating obtained by chemical modification can effectively reduce the friction coefficient of the coating surface and enhance the wear resistance. The organosilicon compound can significantly reduce the internal stress of the epoxy resin, thereby improving the toughness and heat resistance of the bisphenol A epoxy resin coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram of the layer structure of a high temperature resistant bottom support film of the present application.

[0046] Figure 2 It is a schematic structural diagram of an intermediate layer of a high temperature resistant bottom support film of the present application.

[0047] Description of reference numerals:

[0048] 1. Anti-stick coating; 2. First PET layer; 3. Intermediate layer; 4. Second PET layer; 5. Wear-resistant coating; 6. First adhesive layer; 7. Second adhesive layer; 8. Primary isolation strip; 9. Secondary isolation strip. DETAILED DESCRIPTION

[0049] The present application is further described in detail below with reference to the embodiments.

[0050] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0051] Preparation Example

[0052] Preparation of modified polyurethane adhesive layer

[0053] Preparation Example 0-1, a method for preparing a modified polyurethane adhesive layer, is prepared by the following method:

[0054] (1) Preparation of the first component: Under a vacuum degree of less than 0.36 KPa, 45 g of bisphenol A diglycidyl ether was heated to 117° C. to remove moisture for 1.7 h, 0.6 g of the first catalyst was added, and the temperature was gradually increased to 93° C. at a rate of 1° C. / min, and the mixture was stirred for 0.5 h. After the first catalyst was completely dissolved, 70 g of diphenylmethane diisocyanate was added dropwise under vacuum conditions, and the mixture was stirred at a rate of 520 r / min for 4.5 h to obtain modified diphenylmethane diisocyanate;

[0055] (2) Under a vacuum degree of less than 0.36 KPa, 17 g of the first polyol was heated to 110° C. to remove moisture for 1.5 h. When the moisture content was less than 0.06%, the vacuum was released, the mixture was cooled to 35° C., and the modified diphenylmethane diisocyanate prepared in step (1) was added. The mixture was gradually heated to 78° C. at a rate of 1° C. / min, and reacted for 2.7 h. The mixture was cooled to 35° C., and then degassed and sealed for storage.

[0056] (3) Preparation of the second component: 33 g of the second polyol was heated to 105° C. to remove moisture for 2.7 h under a vacuum degree of less than 0.36 KPa. When the moisture content was less than 0.06%, the vacuum was released, and after cooling to 35° C., 0.8 g of the second catalyst, 14 g of the chain extender, 4.5 g of the cross-linking agent, and 1 g of the nano zirconium dioxide powder were added in sequence, mixed, stirred for 30 min, and degassed and sealed for storage;

[0057] (4) mixing the first component and the second component at a vacuum degree of less than 0.36 KPa, wherein the mass ratio of the first component to the second component is 1:0.6, and magnetically stirring at a speed of 290 r / min to obtain a modified polyurethane rubber;

[0058] (5) After the surface of the intermediate layer is pretreated, the modified polyurethane adhesive prepared in step (4) is evenly coated on the intermediate layer, and the first PET layer and the second PET layer are attached to both sides of the intermediate layer. After curing at room temperature for 2.5 hours, a modified polyurethane adhesive layer is obtained.

[0059] Preparation Example 0-2, a method for preparing a modified polyurethane adhesive layer, is prepared by the following method:

[0060] (1) Preparation of the first component: Under a vacuum degree of less than 0.36 KPa, 48 g of bisphenol A diglycidyl ether was heated to 120° C. to remove moisture for 2 h, 0.7 g of the first catalyst was added, and the temperature was gradually increased to 95° C. at a rate of 2° C. / min, and the mixture was stirred for 0.5 h. After the first catalyst was completely dissolved, 80 g of diphenylmethane diisocyanate was added dropwise under vacuum, and the mixture was stirred at a rate of 550 r / min for 5 h to obtain modified diphenylmethane diisocyanate;

[0061] (2) Under a vacuum degree of less than 0.36 KPa, 20 g of the first polyol was heated to 115° C. to remove moisture for 2 h. When the moisture content was less than 0.06%, the vacuum was released, the mixture was cooled to 40° C., the modified diphenylmethane diisocyanate prepared in step (1) was added, the temperature was gradually increased to 80° C. at a rate of 2° C. / min, the mixture was reacted for 3 h, the mixture was cooled to 40° C., the mixture was degassed and sealed for storage;

[0062] (3) Preparation of the second component: 36 g of the second polyol was heated to 110° C. to remove moisture for 3 h under a vacuum of less than 0.36 KPa. When the moisture content was less than 0.06%, the vacuum was released, and after cooling to 40° C., 0.9 g of the second catalyst, 16 g of the chain extender, 6 g of the cross-linking agent, and 1.2 g of the nano zirconium dioxide powder were added in sequence, mixed, stirred for 30 min, and degassed and sealed for storage;

[0063] (4) mixing the first component and the second component at a vacuum degree of less than 0.36 KPa, wherein the mass ratio of the first component to the second component is 1:0.7, and magnetically stirring at a speed of 300 r / min to obtain a modified polyurethane rubber;

[0064] (5) After the surface of the intermediate layer is pretreated, the modified polyurethane adhesive prepared in step (4) is evenly coated on the intermediate layer, and the first PET layer and the second PET layer are attached to both sides of the intermediate layer. After curing at room temperature for 3 hours, a modified polyurethane adhesive layer is obtained.

[0065] Preparation Example 0-3, a method for preparing a modified polyurethane adhesive layer, is prepared by the following method:

[0066] (1) Preparation of the first component: Under a vacuum degree of less than 0.36 KPa, 42 g of bisphenol A diglycidyl ether was heated to 115° C. to remove moisture for 1.5 h, 0.5 g of the first catalyst was added, and the temperature was gradually increased to 90° C. at a rate of 1° C. / min, and the mixture was stirred and mixed for 0.5 h. After the first catalyst was completely dissolved, 60 g of diphenylmethane diisocyanate was added dropwise under vacuum conditions, and the mixture was stirred and reacted at a rate of 500 r / min for 4 h to obtain modified diphenylmethane diisocyanate;

[0067] (2) Under a vacuum degree of less than 0.36 KPa, 15 g of the first polyol was heated to 105° C. to remove moisture for 1 h. When the moisture content was less than 0.06%, the vacuum was released, the mixture was cooled to 30° C., the modified diphenylmethane diisocyanate prepared in step (1) was added, the temperature was gradually increased to 75° C. at a rate of 1° C. / min, the mixture was reacted for 2.5 h, the mixture was cooled to 30° C., the mixture was degassed and sealed for storage;

[0068] (3) Preparation of the second component: Under a vacuum degree of less than 0.36 KPa, 30 g of the second polyol was heated to 100° C. to remove moisture for 2.5 h. When the moisture content was less than 0.06%, the vacuum was released, and after cooling to 30° C., 0.7 g of the second catalyst, 12 g of the chain extender, 3 g of the cross-linking agent, and 0.8 g of the nano zirconium dioxide powder were added in sequence, mixed, stirred for 30 min, and degassed and sealed for storage;

[0069] (4) mixing the first component and the second component at a vacuum degree of less than 0.36 KPa, wherein the mass ratio of the first component to the second component is 1:0.5, and magnetically stirring at a speed of 280 r / min to obtain a modified polyurethane rubber;

[0070] (5) After the surface of the intermediate layer is pretreated, the modified polyurethane adhesive prepared in step (4) is evenly coated on the intermediate layer, and the first PET layer and the second PET layer are attached to both sides of the intermediate layer. After curing at room temperature for 2 hours, a modified polyurethane adhesive layer is obtained.

[0071] Preparation Example 0-4, a method for preparing a modified polyurethane adhesive layer, differs from Preparation Example 0-1 in that bisphenol A diglycidyl ether is not added in step (1).

[0072] Preparation Example 0-5 is a method for preparing a modified polyurethane adhesive layer. The difference from Preparation Example 0-1 is that nano zirconium dioxide powder is not added in step (3).

[0073] Preparation Example 0-6, a method for preparing a modified polyurethane adhesive layer, differs from Preparation Example 0-1 in that the mass ratio of the first component to the second component in step (4) is 1:0.2.

[0074] Preparation Example 0-7, a method for preparing a modified polyurethane adhesive layer, differs from Preparation Example 0-1 in that the mass ratio of the first component to the second component in step (4) is 1:1.

[0075] Preparation of organosilicon-based anti-stick coating modified by organoantimony

[0076] Preparation Example 1-1, a method for preparing an organosilicon-based antimony-modified anti-stick coating, comprising the following steps:

[0077] (1) Mixing methyl vinyl MQ silicone resin with vinyl silicone oil and hydrogen-containing silicone oil in sequence, stirring ultrasonically for 30 minutes, adding Pt catalyst, heating to 38° C., reacting for 35 minutes, and obtaining a liquid reaction solution;

[0078] (2) adding antimony tribenzoate dropwise to the liquid phase reaction solution in step (1), mixing, stirring for 5 minutes, then adding nano-silicon dioxide powder, mixing, stirring for 10 minutes, and standing at room temperature for 30 minutes to obtain a preliminary coating;

[0079] (3) After the first PET layer is subjected to surface pretreatment, the preliminary coating prepared in step (2) is evenly coated on the surface of the first PET layer, dried at 85° C. for 30 min, cured at a constant temperature for 4 h, and naturally cooled to obtain an organic antimony-modified silicone-based anti-stick coating.

[0080] Preparation Example 1-2, a method for preparing an organosilicon-based antimony-modified anti-stick coating, comprising the following steps:

[0081] (1) Mixing methyl vinyl MQ silicone resin with vinyl silicone oil and hydrogen silicone oil in sequence, stirring ultrasonically for 40 minutes, adding Pt catalyst, heating to 40° C., reacting for 40 minutes, and obtaining a liquid reaction solution;

[0082] (2) adding antimony tribenzoate dropwise to the liquid phase reaction solution in step (1), mixing, stirring for 5 minutes, then adding nano-silicon dioxide powder, mixing, stirring for 10 minutes, and standing at room temperature for 30 minutes to obtain a preliminary coating;

[0083] (3) After the first PET layer is subjected to surface pretreatment, the preliminary coating prepared in step (2) is evenly coated on the surface of the first PET layer, dried at 90° C. for 30 min, cured at a constant temperature for 4 h, and naturally cooled to obtain an organic antimony-modified silicone-based anti-stick coating.

[0084] Preparation Example 1-3, a method for preparing an organic antimony-modified organic silicon-based anti-stick coating, comprising the following steps:

[0085] (1) Mixing methyl vinyl MQ silicone resin with vinyl silicone oil and hydrogen-containing silicone oil in sequence, stirring ultrasonically for 20 minutes, adding Pt catalyst, heating to 35° C., reacting for 30 minutes, and obtaining a liquid reaction solution;

[0086] (2) adding antimony tribenzoate dropwise to the liquid phase reaction solution in step (1), mixing, stirring for 5 min, then adding nano-silicon dioxide powder, mixing, stirring for 10 min, and standing at room temperature for 30 min to obtain a preliminary coating;

[0087] (3) After the first PET layer is subjected to surface pretreatment, the preliminary coating prepared in step (2) is evenly coated on the surface of the first PET layer, dried at 80-90° C. for 30 min, cured at a constant temperature for 4 h, and naturally cooled to obtain an organic antimony-modified silicone-based anti-stick coating.

[0088] Preparation Example 1-4 is a method for preparing an organic antimony-modified silicone-based anti-stick coating, which differs from Preparation Example 1-1 in that antimony tribenzoate is not added in step (2).

[0089] Preparation Example 1-5, a method for preparing an organic antimony-modified organic silicon-based anti-stick coating, is different from Preparation Example 1-1 in that no nano-silicon dioxide powder is added in step (2).

[0090] Example

[0091] Embodiment 1, a high temperature resistant support film, the preparation method of the support film comprises the following steps:

[0092] S1, heating the coating of the anti-stick coating to 48° C., applying the coating of the anti-stick coating on the surface of the first PET layer to form an anti-stick coating, then heating the coating of the wear-resistant coating to 65° C., applying the coating of the wear-resistant coating on the surface of the second PET layer to form a wear-resistant coating, and standing the first PET layer and the second PET layer coated with the coating at room temperature for 2.5 hours for curing;

[0093] S2. Coat the side of the first PET layer away from the anti-stick coating with a modified polyurethane adhesive to form a first adhesive layer, then cover the intermediate layer on the first adhesive layer, and coat the side of the second PET layer away from the wear-resistant coating with a modified polyurethane adhesive to form a second adhesive layer, and then bond the side of the second PET layer coated with the second adhesive layer to the side of the intermediate layer away from the first adhesive layer, and hot press the above materials at a temperature of 70° C. and a pressure of 0.4 MPa for 2 seconds to obtain a high temperature resistant base film.

[0094] Among them, the modified polyurethane adhesive layer comes from Preparation Example 0-1, and the organic antimony-modified organic silicon anti-stick coating comes from Preparation Example 1-1.

[0095] The silicone-modified bisphenol A epoxy resin wear-resistant coating is prepared by the following method:

[0096] 1. Mix 10g E 03 bisphenol A epoxy resin and 0.2g triphenylphosphine, stir for 30min, and heat to 70℃ under nitrogen protection. Slowly drop 4ml acrylic acid, heat to 80℃, and react for 4h to obtain a transparent viscous liquid;

[0097] 2. The transparent viscous liquid in step (1) was washed 5 times with distilled water, the upper liquid was removed, and then washed 3 times with acetone and cyclohexane, and the purified liquid was vacuum dried at 30° C. for 8 h to obtain bisphenol A type epoxy acrylic resin;

[0098] 3. Mix 14 g of the bisphenol A epoxy acrylic resin prepared in step (2), 0.2 g of dibenzoyl peroxide and 1.8 ml of methacryloxypropyltrimethoxysilane, and stir at 80° C. for 4 h under nitrogen protection to obtain a prepolymer.

[0099] 4. After the second PET layer is surface pretreated, the prepolymer in step (3) is evenly coated on the surface of the second PET layer, placed at room temperature for 30 minutes, then dried at 50°C for 30 minutes, and cured at a constant temperature for 8 hours. After natural cooling, a silicone-modified bisphenol A epoxy resin wear-resistant coating is obtained.

[0100] Embodiment 2, a high temperature resistant bottom support film, is different from Embodiment 1 in that it comprises the following steps:

[0101] S1, heating the coating of the anti-stick coating to 55° C., applying the coating of the anti-stick coating on the surface of the first PET layer to form an anti-stick coating, then heating the coating of the wear-resistant coating to 70° C., applying the coating of the wear-resistant coating on the surface of the second PET layer to form a wear-resistant coating, and standing the first PET layer and the second PET layer coated with the coating at room temperature for 3 hours for curing;

[0102] S2. Coat the side of the first PET layer away from the anti-stick coating with a modified polyurethane adhesive to form a first adhesive layer, then cover the intermediate layer on the first adhesive layer, and coat the side of the second PET layer away from the wear-resistant coating with a modified polyurethane adhesive to form a second adhesive layer, and then bond the side of the second PET layer coated with the second adhesive layer to the side of the intermediate layer away from the first adhesive layer, and hot press the above materials at a temperature of 80° C. and a pressure of 0.4 MPa for 2 seconds to obtain a high temperature resistant base film.

[0103] Embodiment 3, a high temperature resistant bottom support film, is different from Embodiment 1 in that it comprises the following steps:

[0104] S1, heating the coating of the anti-stick coating to 40° C., applying the coating of the anti-stick coating on the surface of the first PET layer to form an anti-stick coating, then heating the coating of the wear-resistant coating to 60° C., applying the coating of the wear-resistant coating on the surface of the second PET layer to form a wear-resistant coating, and standing the first PET layer and the second PET layer coated with the coating at room temperature for 2 hours for curing;

[0105] S2. Coat the side of the first PET layer away from the anti-stick coating with a modified polyurethane adhesive to form a first adhesive layer, then cover the intermediate layer on the first adhesive layer, and coat the side of the second PET layer away from the wear-resistant coating with a modified polyurethane adhesive to form a second adhesive layer, and then bond the side of the second PET layer coated with the second adhesive layer to the side of the intermediate layer away from the first adhesive layer, and hot press the above materials at a temperature of 60°C and a pressure of 0.3MPa for 1s to obtain a high temperature resistant base film.

[0106] Example 4, a high temperature resistant backing film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-2, and the organic antimony modified organic silicon anti-sticking coating is derived from Preparation Example 1-2.

[0107] Example 5, a high temperature resistant backing film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-3, and the organic antimony modified organic silicon anti-sticking coating is derived from Preparation Example 1-3.

[0108] Example 6, a high temperature resistant base film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-4.

[0109] Example 7, a high temperature resistant base film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-5.

[0110] Example 8, a high temperature resistant base film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-6.

[0111] Example 9, a high temperature resistant base film, is different from Example 1 in that the modified polyurethane adhesive layer is derived from Preparation Example 0-7.

[0112] Example 10, a high temperature resistant support film, is different from Example 1 in that the organic antimony modified organic silicon anti-sticking coating is derived from Preparation Example 1-4.

[0113] Example 11, a high temperature resistant base film, is different from Example 1 in that the organic antimony modified organic silicon anti-sticking coating is derived from Preparation Example 1-5.

[0114] Example 12, a high temperature resistant base film, is different from Example 1 in that step (3) is not performed during the preparation of the silicone-modified bisphenol A epoxy resin wear-resistant coating.

[0115] Comparative Example

[0116] Comparative Example 1 is a high temperature resistant backing film, which is different from Example 1 in that in the preparation method of the modified polyurethane adhesive layer, diphenylmethane diisocyanate (MDI) is replaced by an equal amount of toluene diisocyanate (TDI).

[0117] Comparative Example 2 is a high temperature resistant backing film, which is different from Example 1 in that in the preparation method of the modified polyurethane adhesive layer, diphenylmethane diisocyanate (MDI) is replaced by an equal amount of hexamethylene diisocyanate (HDI).

[0118] Comparative Example 3, a high temperature resistant backing film, is different from Example 1 in that in the preparation method of the modified polyurethane adhesive layer, the first polyol and the second polyol are both replaced by equal amounts of polyoxypropylene glycol (PPG), polyoxypropylene triol, polytetramethylene glycol (PTMG), and tetramethylene glycol-propylene oxide copolymer.

[0119] Comparative Example 4 is a high temperature resistant backing film, which is different from Example 1 in that in the preparation method of the modified polyurethane adhesive layer, the first polyol and the second polyol are both replaced by butadiene acrylonitrile-styrene copolymer polyol in equal amounts.

[0120] Comparative Example 5 is a high temperature resistant backing film, which is different from Example 1 in that in the preparation method of the modified polyurethane adhesive layer, the chain extender is replaced by an equal amount of one or more of ethylene glycol, propylene glycol, trimethylolpropane, 1,4-butanediol, and diethylene glycol.

[0121] Comparative Example 6, a high temperature resistant backing film, is different from Example 1 in that a method for preparing a modified polyurethane adhesive layer comprises the following steps:

[0122] (1) Under a vacuum degree of less than 0.36 KPa, 45 g of bisphenol A diglycidyl ether was heated to 117° C. to remove moisture for 1.7 h, 1.4 g of a first catalyst was added, and the temperature was gradually increased to 93° C. at a rate of 1° C. / min, and the mixture was stirred for 0.5 h. After the first catalyst was completely dissolved, 70 g of diphenylmethane diisocyanate was added dropwise under vacuum conditions, and the mixture was stirred at a rate of 520 r / min for 4.5 h to obtain modified diphenylmethane diisocyanate;

[0123] (2) Under a vacuum degree of less than 0.36 KPa, 50 g of the first polyol was heated to 110° C. to remove moisture for 1.5 h. When the moisture content was less than 0.06%, the vacuum was released. After cooling to 35° C., the modified diphenylmethane diisocyanate prepared in step (1), 14 g of a chain extender, 4.5 g of a cross-linking agent, and 1 g of a nano zirconium dioxide powder were added and mixed. The mixture was magnetically stirred at a speed of 290 r / min, and the temperature was gradually increased to 78° C. at a rate of 1° C. / min. The mixture was reacted for 2.7 h. After cooling to 35° C., a modified polyurethane rubber was obtained.

[0124] (3) After the surface of the intermediate layer is pretreated, the modified polyurethane adhesive prepared in step (2) is evenly coated on the intermediate layer, the first PET layer and the second PET layer are attached to both sides of the intermediate layer, and the modified polyurethane adhesive layer is obtained after curing at room temperature for 2.5 hours.

[0125] Performance testing

[0126] Prepare the bottom film according to the method in each embodiment and each comparative example, and cut each bottom film into several standard squares with a size of 50cm*50cm. The standard squares are tested for heat resistance, peel strength and wear resistance. Among them, three squares are taken for each embodiment or comparative example for testing, and the test results are averaged and recorded in Table 1. The test method is as follows: 1. Heat resistance: Put the standard square to be tested into a high-temperature furnace, set the starting temperature to 100℃ for preheating, and gradually increase the temperature at a rate of 4℃ / min. Observe whether the surface of the standard square in the furnace has discoloration, bubbling and other phenomena, and whether the composite layer structure of the standard square has cracking, segregation and other phenomena, so as to determine the critical tolerance temperature of the sample. The test results are shown in Table 1.

[0127] 2. Peel strength: Referring to GB / T 2970-1995, 30g of high-temperature semi-finished rubber was evenly pressed onto the surface of the first PET layer of the standard block, and then the standard block was tested for peel strength using an electronic peeling machine. The test results are shown in Table 1.

[0128] 3. Wear resistance: A 600-grit sandpaper loaded with a 100-g weight was evenly rubbed on the second PET layer surface of the blank and standard square at a constant speed for 100 times. The weight was weighed every 20 times and the total wear weight loss was calculated. The test results are shown in Table 1.

[0129] Table 1

[0130] Test items Heat resistance(℃) Peel strength (N / m) Wear resistance(g) Example 1 227 4.6 0.53 Example 2 220 5.0 0.57 Example 3 223 5.4 0.61 Example 4 194 5.7 0.63 Example 5 198 5.5 0.65 Example 6 179 4.9 0.57 Example 7 185 5.3 0.56 Example 8 191 5.1 0.60 Example 9 188 5.4 0.58 Example 10 202 11.2 0.64 Embodiment 11 211 9.6 0.59 Example 12 209 6.2 1.21 Comparative Example 1 175 6.1 0.61 Comparative Example 2 153 6.3 0.58 Comparative Example 3 138 5.8 0.60 Comparative Example 4 155 6.1 0.64 Comparative Example 5 177 5.7 0.59 Comparative Example 6 139 6.0 0.61

[0131] In combination with Examples 1-3, Comparative Example 1 and Table 1, the heat resistance of the support film prepared by Examples 1-3 is better than that of the support film prepared by Comparative Example 1. It can be seen from the test results that due to the high reactivity and volatility of toluene diisocyanate (TDI), the viscosity of the modified polyurethane adhesive layer prepared with TDI as the main monomer is relatively low. In addition, the synthesis of polyurethane in the TDI system generally adopts the prepolymer method, while the synthesis of polyurethane in the MDI system often uses a semi-prepolymer method that can effectively reduce the viscosity of the system due to its high system viscosity, thereby effectively reducing the viscosity of the system and making the chain extender and the like mixed evenly. Therefore, the heat resistance of the support films prepared by Examples 1-3 is better than that of the support film prepared by Comparative Example 1, among which the heat resistance of the support film prepared by Example 1 is the best.

[0132] In combination with Examples 1-3, Comparative Example 2 and Table 1, the heat resistance of the support film prepared by Examples 1-3 is slightly better than that of the support film prepared by Comparative Example 2. It can be seen from the test results that since hexamethylene diisocyanate (HDI) is a kind of aliphatic isocyanate, and MDI as an aromatic isocyanate generally has better molecular symmetry, regularity and rigidity, aromatic isocyanates are more heat-resistant than aliphatic isocyanates, and aromatic isocyanates are highly reactive, react faster than aliphatic isocyanates, provide polyurethane rigidity, and have lower oxidation and UV stability. On the other hand, HDI, as the main raw material, is too expensive and difficult to achieve industrial production.

[0133] Combined with Examples 1-3, Comparative Example 3 and Table 1, the heat resistance of the support film prepared by Examples 1-3 is better than that of the support film prepared by Comparative Example 3. It can be seen from the test results that since polyoxypropylene glycol (PPG) and the like belong to polyether polyols, the presence of ether bonds in the configuration of the polyether polyols leads to low cohesive energy, which is conducive to the rotation of single bonds, and the ether bonds are resistant to hydrolysis, so the polyurethane material prepared therefrom can have good flexibility and hydrolysis resistance, but its carbon atoms are easily oxidized, so the thermal stability of the prepared polyurethane material is poor.

[0134] Combining Examples 1-3, Comparative Example 4 and Table 1, the heat resistance of the backing films prepared by Examples 1-3 is better than that of the backing film prepared by Comparative Example 4. It can be seen from the test results that since butadiene acrylonitrile-styrene copolymer polyol belongs to polyolefin polyol, although the polyurethane material synthesized from polyolefin polyol has good hydrolysis resistance and UV resistance, it has low strength and is currently less used.

[0135] Combined with Examples 1-3, Comparative Example 5 and Table 1, the heat resistance of the support film prepared by Examples 1-3 is better than that of the support film prepared by Comparative Example 5. It can be seen from the test results that the heat resistance of the polyurethane material prepared by the amine low molecular weight chain extender is better than that of the polyurethane material prepared by the alcohol low molecular weight chain extender, wherein the amine low molecular weight chain extender is generally added in the emulsification stage, can produce urea bonds to promote the formation of intermolecular hydrogen bonds, has good high temperature resistance, and has high strength and hardness; while the alcohol low molecular weight chain extender is generally added in the prepolymer stage, and when the amount is large, it affects the stability of the emulsion, resulting in a decrease in particle size, but the uniformity in the system is improved, so that the polymer has good hardness and toughness.

[0136] In combination with Examples 1-3, Comparative Example 6 and Table 1, the heat resistance of the support film prepared by Examples 1-3 is better than that of the support film prepared by Comparative Example 6. It can be seen from the test results that Comparative Example 6 adopts a one-step synthesis method to add all components such as isocyanate, polyol, chain extender and other additives at one time, and mix and cast them into a reaction shape at one time. However, the large amount of heat generated in the early stage of the reaction cannot be removed quickly, resulting in an increase in the reaction temperature and a deepening of the side reaction. In addition, due to the one-time addition of the raw materials, the polymerization and chain extension reactions proceed simultaneously. In the later stage of the reaction, the movement space of the molecular chain is limited due to the sharp increase in viscosity, which makes the molecular weight of the polyurethane material lower and the performance of the material poor. The polyurethane material synthesized by the one-step method has an incomplete structure and a polydisperse hard segment length, resulting in poor heat resistance. Embodiments 1-3 all use a semi-prepolymer method, which has the advantage that each step is controllable, so the reaction degree of the raw materials is high, the molecular weight of the obtained polyurethane material is large, the internal structure is relatively complete, and the state of the reaction product is uniform, and the performance of the synthesized product is better. Compared with the one-step synthesis method, the semi-prepolymer method is more suitable for industrial production.

[0137] In combination with Example 1, Example 4, Example 5 and Table 1, the heat resistance of the support film prepared by Example 1 is better than that of the support film prepared by Example 4 and Example 5, and the peel strength of the support film prepared by Example 1 is less than that of the support film prepared by Example 4 and Example 5. It can be seen from the test results that in the modified synthesis reaction of the polyurethane adhesive layer and the silicone anti-stick coating, the amount of reactants added and the reaction conditions are both within the set range. After changing the reaction conditions or the amount of material added is close to the end value, the yield will be affected. Among them, temperature, as a key factor affecting the activation energy of the main and side reactions, directly affects the reaction mechanism of the preparation of polyurethane prepolymers. When the temperature is within the appropriate range, isocyanate can obtain sufficient reaction activity during polymerization, and the steric effect is basically non-existent. However, when the temperature exceeds the appropriate range value, more high molecular weight components will be generated. Since these substances increase the branching points in the reaction system, the viscosity of the prepolymer may increase, and even the gel point of the prepolymer may be changed, resulting in difficulty in separation. And it will also cause the isocyanate group content of the prepolymer to decrease, reducing the subsequent reaction performance.

[0138] Combining Example 1 with Example 6, Example 7 and Table 1, the heat resistance of the support film prepared by Example 1 is better than that of the support films prepared by Example 6 and Example 7. It can be seen from the test results that the isocyanate in Example 6 is not chemically modified by bisphenol A diglycidyl ether, so it is impossible to generate oxazolidinone and introduce it into the polyurethane molecule to increase the thermal decomposition temperature of the polyurethane; in Example 7, the heat-resistant filler nano zirconium dioxide powder is not mixed into the modified polyurethane rubber to achieve physical modification, and the zirconium dioxide material has a high thermal insulation coefficient to improve the high temperature resistance of the polyurethane. And the aromatic diisocyanate is mainly synthesized with toluene as the raw material, contains a benzene ring structure, and therefore also has good heat resistance.

[0139] In combination with Example 1, Example 8, Example 9 and Table 1, the heat resistance of the bottom film prepared by Example 1 is better than that of the bottom film prepared by Example 6 and Example 7. It can be seen from the test results that when preparing polyurethane by the semi-prepolymer method, the ratio between the first component and the second component will directly affect the synthesis quality of the soft segment and the hard segment in the polyurethane long chain. Since polyurethane is a multi-block copolymer with alternating soft and hard segments prepared by step-by-step polymerization, the soft segment provides the low-temperature performance, elongation at break and elasticity of the polyurethane, while the hard segment gives the polyurethane material properties such as modulus, strength and heat resistance. Therefore, controlling the ratio between the first component and the second component within a suitable range is particularly critical for the performance of the prepared polyurethane material.

[0140] Combining Example 1 with Example 10, Example 11 and Table 1, the peel strength of the support film prepared by Example 1 is less than the peel strength of the support film prepared by Example 10 and Example 11. It can be seen from the test results that the organic silicon-based anti-stick coating prepared in Example 10 is not chemically modified by adding the high temperature resistant filler antimony tribenzoate, and the organic antimony heat-resistant material has excellent initial aging resistance and thermal stability. Therefore, the anti-stick coating on the support film prepared in Example 10 shows instability at high temperature, and the uniformity of the coating is easily destroyed, and the expected anti-stick effect cannot be achieved; the support film prepared in Example 11 shows the worst anti-stick effect. Since nano-silicon dioxide powder is not added, the surface roughness of the coating cannot be changed by nano-silicon dioxide powder, thereby reducing the surface free energy of the coating to achieve the expected anti-stick effect.

[0141] Combining Example 1, Example 12 and Table 1, the wear resistance of the support film prepared by Example 1 is significantly better than that of the support film prepared by Example 12. It can be seen from the test results that Example 12 does not use an organosilicon compound to modify the bisphenol A epoxy resin, resulting in a larger friction coefficient of the obtained coating surface, so the wear resistance is reduced.

[0142] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high temperature resistant bottom support film, characterized in that: The invention comprises, from the inside to the outside, an anti-stick coating (1), a first PET layer (2), an intermediate layer (3), a second PET layer (4) and a wear-resistant coating (5); a first adhesive layer (6) is arranged between the first PET layer (2) and the intermediate layer (3); a second adhesive layer (7) is arranged between the second PET layer (4) and the intermediate layer (3); the anti-stick coating (1) is attached to the first PET layer (2); and the wear-resistant coating (5) is attached to the second PET layer (4); and the first adhesive layer and the second adhesive layer are both modified polyurethane adhesive layers; and the wear-resistant coating (5) is a silicone-modified bisphenol A epoxy resin wear-resistant coating; The modified polyurethane adhesive layer comprises a first component and a second component, wherein the first component comprises the following raw materials by weight: 60-80 parts of diphenylmethane diisocyanate, 42-48 parts of bisphenol A diglycidyl ether, 15-20 parts of a first polyol and 0.5-0.7 parts of a first catalyst; the second component comprises the following raw materials by weight: 30-36 parts of a second polyol, 12-16 parts of a chain extender, 0.7-0.9 parts of a second catalyst, 3-6 parts of a crosslinking agent and 0.8-1.2 parts of a nano zirconium dioxide powder; The method for preparing the modified polyurethane adhesive layer comprises the following steps: S1. Preparation of the first component: Under a vacuum degree of less than 0.36 KPa, bisphenol A diglycidyl ether is heated to 115-120°C to remove moisture for 1.5-2 hours, a first catalyst is added, and the temperature is gradually increased to 90-95°C at a rate of 1-2°C / min, and stirred for 0.5 hours. After the first catalyst is completely dissolved, diphenylmethane diisocyanate is added dropwise under vacuum conditions, and the reaction is stirred at a speed of 500-550 r / min for 4-5 hours to obtain modified diphenylmethane diisocyanate; S2. Under a vacuum degree of less than 0.36 KPa, heat the first polyol to 105-115°C to remove moisture for 1-2 hours. When the moisture content is less than 0.06%, release the vacuum, cool to 30-40°C, add the modified diphenylmethane diisocyanate prepared in step S1, gradually heat to 75-80°C at a rate of 1-2°C / min, react for 2.5-3 hours, cool to 30-40°C, degas and seal for storage; S3, preparation of the second component: under a vacuum degree of less than 0.36 KPa, heat the second polyol to 100-110°C to remove moisture for 2.5-3h, when the moisture mass is less than 0.06%, release the vacuum, cool to 30-40°C, add the second catalyst, chain extender, crosslinking agent and nano zirconium dioxide powder in sequence, mix, stir for 30min, degas and seal for storage; S4, mixing the first component and the second component at a vacuum degree below 0.36 KPa, wherein the mass ratio of the first component to the second component is 1:(0.5-0.7), and magnetically stirring at a speed of 280-300 r / min to obtain a modified polyurethane rubber; S5, after pre-treating the surface of the intermediate layer, uniformly coating the modified polyurethane adhesive prepared in step S4 on the intermediate layer, attaching the first PET layer and the second PET layer to both sides of the intermediate layer, and curing at room temperature for 2-3 hours to obtain the modified polyurethane adhesive layer; The anti-stick coating (1) is an organic antimony-modified organic silicon-based anti-stick coating, and the organic antimony-modified organic silicon-based anti-stick coating comprises the following components in parts by weight: 15-20 parts of methyl vinyl MQ silicone resin, 4-7 parts of vinyl silicone oil, 2-3 parts of hydrogen-containing silicone oil, 0.3-0.7 parts of antimony tribenzoate and 0.5-0.8 parts of nano-silicon dioxide powder; The method for preparing the organosilicon-based antimony-modified anti-stick coating comprises the following steps: S1, mixing methyl vinyl MQ silicone resin with vinyl silicone oil and hydrogen-containing silicone oil in sequence, stirring ultrasonically for 20-40 minutes, adding Pt catalyst, heating to 35-40° C., reacting for 30-40 minutes, and obtaining a liquid phase reaction solution; S2, first add antimony tribenzoate to the liquid phase reaction solution in step S1, mix, stir for 5 minutes, then add nano silicon dioxide powder, mix, stir for 10 minutes, and stand at room temperature for 30 minutes to prepare a preliminary coating; S3, after the surface of the first PET layer is pretreated, the preliminary coating prepared in step S2 is evenly coated on the surface of the first PET layer, dried at 80-90° C. for 30 min, cured at a constant temperature for 4 h, and naturally cooled to obtain an organic antimony-modified silicone-based anti-stick coating.

2. A high temperature resistant bottom support film according to claim 1, characterized in that: The intermediate layer comprises primary isolation strips (8) and secondary isolation strips (9) which are arranged in a staggered manner, wherein the primary isolation strips (8) intersect with each other to form a 5 mm×5 mm grid structure, and the primary isolation strips (8) are arranged to be a polyurethane material, and the secondary isolation strips (9) are arranged to be a silicon oxide nanofiber material.

3. The high temperature resistant bottom support film according to claim 1, characterized in that: The first polyol and the second polyol are both one or more of polyethylene adipate diol and polycarbonate diol.

4. The high temperature resistant bottom support film according to claim 1, characterized in that: The chain extender is one or more of diethanolamine and triethanolamine.

5. The high temperature resistant bottom support film according to claim 1, characterized in that: The first catalyst and the second catalyst are both one or more of dimethylcyclohexylamine, dimethylethanolamine and triethylenediamine.

6. The high temperature resistant bottom support film according to claim 1, characterized in that: The crosslinking agent is diethylenetriamine.

7. A method for preparing a high temperature resistant support film according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, heating the coating of the anti-stick coating (1) to 40-55°C, coating the coating of the anti-stick coating (1) on the surface of the first PET layer (2) to form the anti-stick coating (1), then heating the coating of the wear-resistant coating (5) to 60-70°C, coating the coating of the wear-resistant coating (5) on the surface of the second PET layer (4) to form the wear-resistant coating (5), and allowing the first PET layer (2) and the second PET layer (4) coated with the coating to stand and cure at room temperature for 2-3 hours; S2. The first PET layer (2) is coated with a modified polyurethane adhesive on the side facing away from the anti-stick coating (1) to form a first adhesive layer (6), and the intermediate layer (3) is then covered on the first adhesive layer (6). The second PET layer (4) is coated with a modified polyurethane adhesive on the side facing away from the wear-resistant coating (5) to form a second adhesive layer (7). The side of the second PET layer (4) coated with the second adhesive layer (7) is then bonded to the side of the intermediate layer (3) facing away from the first adhesive layer (6). The above materials are hot-pressed at a temperature of 60-80° C. and a pressure of 0.3-0.4 MPa for 1-2 seconds to obtain a high temperature resistant backing film.